Penta Helix Collaboration in Developing Social Inclusion for Persons with Disabilities - Ismi Dwi Astuti Nurhaeni; Intan Sani Putri; Asal Wahyuni Erlin Mulyadi; Desiderius Priyo Sudibyo (Journal of Contemporary Governance and Public Policy, 2024)
This research examines collaboration between the government, community, academia, entrepreneurs and the media, known as the ‘penta helix’, in developing social inclusion for persons with disabilities (PwD) in Indonesia. This descriptive and qualitative study collects data through observation, focus group discussions and in-depth interviews. The research informants were determined purposively from representatives of the penta helix who were seen as understanding or having the authority to interact with PwD. For data analysis, Miles and Huberman’s interactive analysis model was employed. Regarding the five areas of the penta helix, the study found that the government exercised political power through the issuance of Regional Regulation 9 of 2020 concerning the protection and fulfilment of the rights of PwD. The regulation aims to ensure that PwD receive the same rights and opportunities as other citizens. The community has a role as social power through creating care classes for PwD for people to understand the culture and self-development of PwD. Academics function as a knowledge power by developing campus inclusion standards and collaborating with national and international funding institutions to carry out the three pillars of higher education on the issue of PwD. Industry plays a role as social justice power in supporting the provision of venture capital assistance and work skills training for PwD. The media holds the power of brand image so that discriminatory views against PwD transform into fulfilling the rights of PwD. Understanding stakeholders’ role in the penta helix collaboration helps develop a social inclusion model for PwD.